2006
DOI: 10.1074/jbc.m604469200
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the Thiazole Biosynthetic Enzyme THI1 from Arabidopsis thaliana

Abstract: Thiamin pyrophosphate is an essential coenzyme in all organisms that depend on fermentation, respiration or photosynthesis to produce ATP. It is synthesized through two independent biosynthetic routes: one for the synthesis of 2-methyl-4-amino-5-hydroxymethylpyrimidine pyrophosphate (pyrimidine moiety) and another for the synthesis of 4-methyl-5-(␤-hydroxyethyl) thiazole phosphate (thiazole moiety). Herein, we will describe the three-dimensional structure of THI1 protein from Arabidopsis thaliana determined by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
60
0
5

Year Published

2008
2008
2017
2017

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 58 publications
(67 citation statements)
references
References 42 publications
2
60
0
5
Order By: Relevance
“…The region spans three BACs and contains seven genes with predicted ORFs (bottom). The thi2-blk Mutant Is Deficient in Thiamine Accumulation THI2 homologs from yeast (THI4) and Arabidopsis (THI1) copurify with ADT, a thiazole precursor to thiamine (Godoi et al, 2006;Jurgenson et al, 2006). Furthermore, the maize THI2 paralog, THI1, rescues the growth defects of yeast thi4 mutants, suggesting a conserved function during thiamine biosynthesis (Belanger et al, 1995).…”
Section: Thi2 Is a Plastid-localized Proteinmentioning
confidence: 99%
“…The region spans three BACs and contains seven genes with predicted ORFs (bottom). The thi2-blk Mutant Is Deficient in Thiamine Accumulation THI2 homologs from yeast (THI4) and Arabidopsis (THI1) copurify with ADT, a thiazole precursor to thiamine (Godoi et al, 2006;Jurgenson et al, 2006). Furthermore, the maize THI2 paralog, THI1, rescues the growth defects of yeast thi4 mutants, suggesting a conserved function during thiamine biosynthesis (Belanger et al, 1995).…”
Section: Thi2 Is a Plastid-localized Proteinmentioning
confidence: 99%
“…While the reaction catalyzed by the thiazole synthase (THI4) has not yet been fully reconstituted, the enzyme copurified with three tightly bound metabolites (35, 40 and 41) and the structure of the enzyme complexed to 41 has been determined. [12][13][14][15] The identity of these metabolites suggested that NAD is the precursor to the thiazole. This was confirmed by the identification of three partial reactions catalyzed by the C204A mutant of THI4 (28 to 29, 29 to 30 and 29 to 35 in Figure 5).…”
Section: Thiamin Biosynthesis In Saccharomyces Cerevisiaementioning
confidence: 99%
“…Em Arabidopis thaliana, o gene thi1 está relacionado com a via da biossíntese de tiamina, sendo composto por uma ORF de 1047 pares de bases, e codifica uma proteína de 349 resíduos de aminoácidos (9). A dedução da sequência polipeptídica da proteína THI1 revelou um alto grau de identidade com as proteínas envolvidas na biossíntese de tiamina em Saccharomyces cerevisiae (51,7% de identidade) e Schizosaccharomyces pombe (55,1% de identidade) (10).…”
unclassified